Tinjauan Sistem Penyelenggaraan Rekam Medis Menurut Standart Akreditasi Puskesmas di Puskesmas Pangakalan Berandan Tahun 2020 - Esraida Simanjuntak; Fajar Insani (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
Puskesmas are required to maintain medical records containing data and information on patient care. Implementation according to accreditation standards, namely criteria 3.2 Registration Process and 3.8 Administration of medical records which are divided into 3.8.1 Coding, 3.8.2 Medical Record Access Rights 3.8.3 Clinical Information Filling and 3.8.4 Storage. The purpose of the study was to find out the implementation of the medical record management system according to the Puskesmas accreditation standards at the Pangkalan Berandan Health Center in 2020. This type of research was qualitative with a Phenomenology approach. The place of research was conducted at the Pangkalan Berandan Health Center. Time of study in July 2020. Research population is all medical record officers at the Pangkalan Berandan Health Center. The research sample is 5 officers. The research instrument was interview guide and check list sheet for observation. The results of the study revealed that the outpatient registration process had been carried out according to criteria 3.2 but there was no inpatient numbering of medical records. Coding was not carried out according to criteria 3.8.1, namely the absence of coding SOPs carried out by doctors using ICD 10, Medical Record Access Rights were carried out according to criteria 3.8. 2 but the implementation is not fully carried out in accordance with the SOP, the lending process is not recorded in the expedition book, Assembling is in accordance with criteria 3.8.3 but recording corrections are carried out using stip-ex and the storage process has been carried out according to criteria 3.8.4 but retention is not carried out according to the guidelines legislation. It is recommended for registration to give medical record numbers to inpatients, coding to make SOPs and given coding training, access rights to medical records to record loans in expedition books, assembling to be given socialization in terms of correcting recording of medical record files and storing tracers as well as in the retention process. given socialization about the implementation of retention.